Factors That Influence Employee Performance at PT. Regional Drinking Water Company of Padang City - Dike Rama Putra; Rahmatullah Pratama (Journal of Innovative and Creativity, 2026)
This study examines the influence of compensation, career development, and communication on employee performance at PT. Regional Water Company Padang City. As a public service provider, the company relies on optimal employee performance to ensure efficient and reliable water distribution services. A quantitative research approach was employed using a survey method, with data collected through structured questionnaires distributed to employees across various units. The variables studied include compensation, career development, communication, and employee performance. Data were analyzed using multiple linear regression to determine the partial and simultaneous effects of each independent variable on performance. The results show that compensation, career development, and communication each have a significant positive effect on employee performance. Among these variables, career development demonstrates the strongest influence, indicating the critical role of professional growth opportunities in enhancing work outcomes. The study concludes that improving compensation systems, strengthening career development programs, and fostering effective communication can significantly enhance employee performance. Recommendations for management and suggestions for further research are provided.